Isolation and Characterization of Aeromonas salmonicida Phage TSW001 and Its Application on Large Yellow Croaker - Jun Yan; Zhenghao Guo; Jing Xie (Foods)
Aeromonas salmonicida is a common spoilage bacterium found in refrigerated fish. In this study, a virulent bacteriophage was isolated from wastewater using A. salmonicida AS08 as the host, and it was designated as TSW001. Based on morphological characterization and whole-genome analysis, bacteriophage TSW001 was classified within the genus Tedavirus. Biological characterization revealed that TSW001 maintained a stable titer within a temperature range of 4~60 °C, a pH range of 4~9, and a salinity range of 50~1000 mM. The optimal multiplicity of infection (MOI) for TSW001 was 0.1, with a short latency period of approximately 10 min and a burst size of approximately 68 PFU/cell. When applied during the cold storage of large yellow croaker, the A. salmonicida count in the fish juice decreased by approximately 2.1~2.3 log10 CFU/mL over the first two days, while the count in the fish fillets decreased by approximately 1.1~1.8 log10 CFU/g. Furthermore, TSW001 demonstrated the ability to inhibit the formation of A. salmonicida biofilms. These results suggest that phage TSW001 is a promising biological antimicrobial agent for controlling A. salmonicida during the cold storage of seafood.